2015
DOI: 10.1002/cmmi.1649
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]‐HP‐DO3A‐nitroimidazole: a promising agent for PET detection of tumor hypoxia

Abstract: The goal of this study is to evaluate a new 68Ga-based imaging agent for detecting tumor hypoxia using positron emission tomography (PET). The new hypoxia targeting agent reported here, [68Ga]-HP-DO3A-nitroimidazole ([68Ga]-HP-DO3A-NI), was constructed by linking a nitroimidazole moiety with the macrocyclic ligand component of ProHance®, HP-DO3A. The hypoxia targeting capability of this agent was evaluated in A549 lung cancer cells in vitro and in SCID mice bearing subcutaneous A549 tumor xenografts. The cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Since 68 Ga-nitroimidazoles are more hydrophilic [9,13], compared with 18 F-FMISO, it was anticipated that the LMR would be higher in the current study and that uptake would be more intense [13]. However, the findings align with Wu et al [14], who raised the concern that the hydrophilicity may lead to insufficient retention and accumulation in hypoxic cells [14]. Furthermore, hypoxia PET/CT is known to have inherently low signal-to-noise ratios [56].…”
Section: Tuberculosis As a Bacterial Tumoursupporting
confidence: 65%
“…Since 68 Ga-nitroimidazoles are more hydrophilic [9,13], compared with 18 F-FMISO, it was anticipated that the LMR would be higher in the current study and that uptake would be more intense [13]. However, the findings align with Wu et al [14], who raised the concern that the hydrophilicity may lead to insufficient retention and accumulation in hypoxic cells [14]. Furthermore, hypoxia PET/CT is known to have inherently low signal-to-noise ratios [56].…”
Section: Tuberculosis As a Bacterial Tumoursupporting
confidence: 65%
“…HBED-CC has been successfully applied in the theranostics of prostate cancer when conjugated to the prostate-specific membrane antigen (PSMA) (Virgolini et al, 2017 ) but the combination with oxygen sensitive groups is yet to been investigated. Gallium-68 labeled nitroimidazole complexes were studied in mice models with induced (xenografted) tumors for CT26 (colon cancer) (Seelam et al, 2015 ), A549 (Wu et al, 2015 ) or 3LL (Fernández et al, 2013 ) (lung cancer cell lines). The comparison with [ 18 F]F-FMISO revealed successful hypoxia imaging and improved clearance properties.…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…also confirmed that the 68 Ga marker could help in the visualization of tumor tissues and hypoxic areas within 2 h of intravenous injection ( 195 ). In short, studies on lung ( 196 ) and colon cancers ( 197 , 198 ) show that on the basis of the ease in production, 68 Ga-labeled hypoxia tracers are comparable to traditional 18 F-labeled tracers.…”
Section: Existing Researchmentioning
confidence: 99%